2022
DOI: 10.1093/bbb/zbac059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage after heating on odor of muscles of yellowtail (Seriola quinqueradiata)

Abstract: Effects of storage after heating on the odor of yellowtail Seriola quinqueradiata muscle was investigated. Sensory evaluation demonstrated odor degradation during storage of ordinary muscle (OM) as well as dark muscle (DM). First, different volatile profiles between OM (dorsal and ventral) and DM; their profiles were also different between non-stored samples (raw samples and just-heated samples) and stored samples except for a part of stored OM. Although the dorsal and ventral OM s differed in lipid content, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…When reheated after 7 days of storage, the sensory evaluation scores of three groups increased, indicating the odorous smell was stronger compared with that without storage. This result was consistent with that reported by Mukojima et al, 2022 , who studied the effects of reheating after storage on the odor of yellowtail fish muscles. They found that the intensity of muscle odor increased with an increase in the number of storage days.…”
Section: Resultssupporting
confidence: 93%
“…When reheated after 7 days of storage, the sensory evaluation scores of three groups increased, indicating the odorous smell was stronger compared with that without storage. This result was consistent with that reported by Mukojima et al, 2022 , who studied the effects of reheating after storage on the odor of yellowtail fish muscles. They found that the intensity of muscle odor increased with an increase in the number of storage days.…”
Section: Resultssupporting
confidence: 93%
“…The injection port, ion source, and transfer line were set at 250 • C, 200 • C, and 250 • C, respectively. TBARS were measured according to the method of Mukojima et al [28].…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…The extracted volatiles were measured using GC according to our previous study [28] but as follows. GCMS transfer lines were maintained at 200 • C. Masses range and scan rate were set at 40-200 m/z and 2.0 scan/s, respectively.…”
Section: Solid Phase Micro Extraction and Gas Liquid Chromatography-m...mentioning
confidence: 99%
“…Yellowtail (Seriola quinqueradiata) is a pelagic migratory fish that inhabits warm-temperate waters and is widely distributed around the world (Mukojima et al, 2022). It is rich in superior protein, polyunsaturated fatty acids, and minerals necessary for human metabolism (Mukojima et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Yellowtail ( Seriola quinqueradiata ) is a pelagic migratory fish that inhabits warm‐temperate waters and is widely distributed around the world (Mukojima et al ., 2022). It is rich in superior protein, polyunsaturated fatty acids, and minerals necessary for human metabolism (Mukojima et al ., 2023). Due to its nutritional value, large size, rapid growth, and delicious taste, it has become an important aquaculture species for the development of deep‐sea fish in China.…”
Section: Introductionmentioning
confidence: 99%